A survey of player monitoring approaches and microsensor use in basketball - Fox, J. L.; Scanlan, A.; Sargent, C.; Stanton, R. (Journal of Human Sport & Exercise, 2020)
The purpose of this study was to examine player monitoring approaches used by basketball practitioners with a specific focus on the use of microsensors. An online survey was disseminated to basketball practitioners via international basketball-related organisations and social media channels. Multiple response, Likert-scale level of agreement, and open-ended questions captured data regarding if, and how player monitoring was performed, as well as barriers and facilitators to player monitoring, with an emphasis on the use of microsensors. Forty-four basketball practitioners completed the survey. Twenty-seven respondents (61%) implement player monitoring and thirteen (30%) use microsensors. Despite implementing player monitoring, over 85% of practitioners modify training based on their own observation. Respondents not currently monitoring players (39%) would commence monitoring if the tools or equipment were provided. 74% of respondents agree that microsensors are expensive. Only 56% of practitioners who use microsensors feel they have support for using the technology and analysing/interpreting the data. These findings suggest a low uptake of microsensors for player monitoring in basketball. Coaches and practitioners perceive player monitoring approaches to be cost-prohibitive and appear unsure of how player monitoring data should be used to optimise training outcomes for players.